Analysis of Pattern of Expression of Immunohistochemical Markers p16, p53 and Ki67 on Cervical Lesions and its Correlation with Histopathology - Renuka Gahine; Varsha Pandey; Megha Gajendra; Pranali K Shende (Journal of Medical Sciences and Health)
Objectives: To study spectrum of cervical lesions on histopathology and its pattern of expression of IHC markers and their correlation with histopathology. Methods: The study was conducted in Department of Pathology at tertiary care hospital, Raipur, Chhattisgarh India; between November 2018 to April 2020. Histopathology of 100 biopsies of cervical lesions were included and categorized into inflammatory, precancerous, and invasive carcinomas and subjected to IHC p16, p53 and Ki67. Statistical analysis was carried out as qualitative study using chi-square test. All diagnostic tests of these markers were calculated and p value<0.05 is considered as level of significance. Results: In present study the pattern of expression of all these three markers showed significant correlation with different spectrum of cervical lesions, with the maximum correlation was seen in Ki67 (0.914*) followed by p16 (0.901*) and p53 (0.524*). The sensitivity and accuracy were maximum in Ki67 i.e. 96.7% and 96% respectively, followed by p16 (sensitivity 94.5% and accuracy 94%) and p53 (sensitivity 76.9% and accuracy 79%) respectively. Ki67 is an extremely sensitive marker to evaluate the proliferative potential of the precancerous as well as cancerous lesion of the cervix [*Pearson correlation]. Conclusion: Expression of these markers increases as the severity of the disease progresses from dysplasia to carcinoma. These biomarkers could be used as an adjunct with histopathological diagnosis, in the evaluation of the proliferative activity, severity and progressive potential.